2012
DOI: 10.1007/s11357-012-9495-6
|View full text |Cite
|
Sign up to set email alerts
|

BDNF transcripts, proBDNF and proNGF, in the cortex and hippocampus throughout the life span of the rat

Abstract: Neurotrophins are established molecular mediators of neuronal plasticity in the adult brain. We analyzed the impact of aging on brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) protein isoforms, their receptors, and on the expression patterns of multiple 5′ exon-specific BDNF transcripts in the rat cortex and hippocampus throughout the life span of the rat (6, 12, 18, and 24 months of age). ProNGF was increased during aging in both structures. Mature NGF gradually decreased in the cortex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 49 publications
(53 reference statements)
3
44
0
Order By: Relevance
“…In contrast, there was no decrease with age in the mature form (mBDNF) which is cleaved from proBDNF. This finding is similar to that reported in rat brain where aging had a specific effect on the level of proBDNF without affecting mBDNF levels (Perovic et al 2013). In the subcortical white matter, there were no significant changes in either proBDNF or mBDNF which is consistent with the lack of significant alteration at the mRNA level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, there was no decrease with age in the mature form (mBDNF) which is cleaved from proBDNF. This finding is similar to that reported in rat brain where aging had a specific effect on the level of proBDNF without affecting mBDNF levels (Perovic et al 2013). In the subcortical white matter, there were no significant changes in either proBDNF or mBDNF which is consistent with the lack of significant alteration at the mRNA level.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, we were unable to determine if the trends and changes in mRNA and protein expression are truly linear across the entire life span or if or where there may be a middle age break point. This is important because in the rat, studies have found a transient decrease in the p75 NGFR receptor protein at 12 and 18 months of age with recovery of expression at 24 months to levels similar to 6 months of age (Perovic et al 2013). Hence, we cannot determine if regulation of the p75 NGFR protein in the rhesus monkey is similar to that in the rat.…”
Section: Discussionmentioning
confidence: 94%
“…NGF plays an important role in maintaining neuronal proliferation and growth of neurons by interacting with other growth factors, and maintenance of cholinergic neurons and memory-related parts of CNS (e.g., hippocampus) (174). A drop in NGF levels with aging has been reported in many animal models (175)(176)(177), which could be an indication of the beneficial effects of NGF in AD patients. However, recent studies have not revealed a significant difference in blood, CSF, and brain levels of NGF in AD patients compared to healthy subjects (178).…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…(C) Timelines for the brain developmental processes important for the functions of neuronal and various glial cells. in different brain regions, with the DAergic and GABAergic systems of the cortex developing late (Tseng et al, 2007;Hashimoto et al, 2009;Kilb, 2012;Manitt et al, 2013;Ouellet and de Villers-Sidani, 2014). Fourth, various neurotrophic factors and their receptors have differential expression profiles in various brain regions (Perovic et al, 2013). Thus, the prolonged effects of drugs of abuse are also dependent on the developmental time of the exposure to drugs (Stanwood and Levitt, 2004).…”
Section: E Developmental Maturation Of the Brain In Rodents And Humansmentioning
confidence: 99%